Editorial - K.Vijayaragavan, (Indian Journal of Extension Education, 2025)
Research and Extension ScholarshipThe issue of improving the scholarship in research and extension is more important in the changing context of' The extension professionals of our country have to improve their scholarship and scholarly practices so that the discipline and practice of extension education will continue to be more relevant and effective in making impacts in agricultural and rural development. Majority of the present-day extension professionals lack a scholarly mentality and as a result, their professional outputs are far below the required standards. There is a need for a stronger drive to improve the quality of teaching, research, and extension activities. As you know that, the idea of scholarship should not be interpreted too, narrowly. often people identify scholarship only with original research. In Scholarship Reconsidered, Boyer wrote: ..Here, then, is our conclusion. What we urgently need today is a more inclusive view of what it means to be a scholar - a recognition that knowledge is acquired through research, through synthesis, through practice, and through teaching. We acknowledge that these four categories - the scholarship of discovery, of integration, of application, and of teaching - divide intellectual functions that are tied inseparably to each other. Still, there is value, we believe, in analyzing the various kinds of academic work, while also acknowledging that they dynamically interact, forming an interdependent whole. Such a vision of scholarship, one that recognizes the great diversity of talent within the professoriate, also may prove especially useful to faculty as they reflect on the meaning and direction of their professional lives" (pp. z4-25). Theodore R. Alterm (2003) has identified six key challenges for extension or outreach scholarship, which reflect where current scholarship is falling short. These challenges include: (1) achieving a scholarly mentality; (2) broadening our view of scholarship as philosophy and concept; (3) understanding the scholarship of engagement; (4) conducting research on the scholarship of engagement; (5)developing and implementing action proposals for change, and (6) developing tools to assess and document outreach scholarship.The future of extension discipline and practices depends upon the improvement of research and extension scholarship.Let us resolve to make necessary changes to achieve it.' Many of the articles in this issue are notable for their usefulness to or implications for extension. you will find a total of eleven research articles and eighteen research notes dealing with various issues such as adopter categorization, organics farming, leadership styles, development orientation, traditional media and the impact of mechanization. I hope that you will have time to read and learn from them. I sincerely extend my thanks to Dr.Premlata Singh, Dr.Rashami Singh, and Dr. R.N. Padaria for their untiring help in bringing out this issue.(K.Vijayaragavan)Chief Editor